2017
DOI: 10.1002/adom.201700238
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Color‐Tunable Solution‐Processed Organic Thin‐Film Laser with a Polymeric Top‐Layer Resonator

Abstract: as a laser resonator, have found a variety of applications in spectroscopy, [5] optical communications, [6] and sensing. [7][8][9][10] DFB lasers can provide narrow single mode emission (linewidth <1 nm) and require only low pump energy for their operation, i.e., they show a low threshold. The resonator is easily integrated into other devices, and it can be implemented with field-effect-transistor geometry, which promises potential for the development of electrically pumped TFOLs. Moreover, DFB lasers can be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 56 publications
(114 reference statements)
3
62
1
Order By: Relevance
“…This value is significantly lower than that of previously reported devices based on COPV1 dispersed in PS with gratings engraved on inorganic substrates . Importantly, the threshold obtained for device R Top NS ( 1 ) is around the same than that obtained with the best lasers with a top‐layer resonator architecture based on COPV3, emitting in similar spectral region …”
Section: Dfb Lasers Based On Poly‐copv1 Filmsmentioning
confidence: 59%
See 3 more Smart Citations
“…This value is significantly lower than that of previously reported devices based on COPV1 dispersed in PS with gratings engraved on inorganic substrates . Importantly, the threshold obtained for device R Top NS ( 1 ) is around the same than that obtained with the best lasers with a top‐layer resonator architecture based on COPV3, emitting in similar spectral region …”
Section: Dfb Lasers Based On Poly‐copv1 Filmsmentioning
confidence: 59%
“…It should simultaneously achieve various characteristics such as high‐quality films with strong photoabsorption (and hence high gain), high photoluminescence quantum yield (PLQY), low waveguide loss, and high photostability. In previous work, it was demonstrated that carbon‐bridged oligo( p ‐phenylenevinylene) dyes (COPV n , with n = 1–6), dispersed in polystyrene (PS), are among the best dyes to be used for DFB lasers emitting at wavelengths that cover a wide range of the visible spectrum (380–600 nm) . Films doped with COPV n , with between 3 and 6 repeat units ( n ), emitting within the 515–585 nm spectral range, exhibited very low amplified spontaneous emission (ASE) and DFB pump intensity thresholds (down to 0.7 kW cm −2 ) and very long operational lifetimes (up to 10 6 pump pulses (pp)).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The slope efficiency of 7.3% was reported for the holographic DFB waveguide laser device with the electroluminescent conjugate polymer of poly[(9,9‐(dihexyl)‐9H‐fluorene‐2,7‐vinylene)‐co‐(1‐methoxy‐4‐(2‐ethylhexyloxy)‐2,5‐phenylene‐vinylene)] (Poly(DH‐PFV‐co‐MEHPPV)) . More recently, the effect of top layer DFB resonator on the laser performances of threshold and slope efficiency were evaluated: the threshold of 1 kW cm −2 (0.1 µJ pulse −1 , 10 µJ cm −2 ) and the slope efficiency of 1.4% were reported …”
Section: Introductionmentioning
confidence: 98%